2006
DOI: 10.1088/1748-6041/1/1/004
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between the adsorption and covalent binding of human immunoglobulin and lysozyme on surface-modified poly( tert -butyl methacrylate)

Abstract: The adsorption and covalent immobilization of human immunoglobulin (HIgG) and lysozyme (LYZ) on surface-modified poly(tert-butyl methacrylate) PtBMA films have been evaluated using x-ray photoelectron spectroscopy (XPS), ellipsometry and atomic force microscopy (AFM). Surface modification of PtBMA (UV irradiation) afforded surfaces suitable for both the physical and covalent attachment of proteins. The XPS and ellipsometry results showed good correlation in terms of variable-dense/thickness protein layer forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
(73 reference statements)
2
7
0
Order By: Relevance
“…It is noteworthy that a similar result was observed for streptavidin molecules, where the binding density of the protein on the SAMs via EDC/NHS reaction was much lower than that by the affinity-based reaction [35]. Other proteins such as immunoglobulin G and lysozyme also showed a notable binding on the polymerized film, compared to the covalent conjugation [36]. This result clearly indicates that the electrostatic interactions on the homogeneous anionic SAMs are mainly responsible for high surface density of PGG-GDH and this might bring higher detection sensitivity in the glucose sensing.…”
Section: Resultssupporting
confidence: 65%
“…It is noteworthy that a similar result was observed for streptavidin molecules, where the binding density of the protein on the SAMs via EDC/NHS reaction was much lower than that by the affinity-based reaction [35]. Other proteins such as immunoglobulin G and lysozyme also showed a notable binding on the polymerized film, compared to the covalent conjugation [36]. This result clearly indicates that the electrostatic interactions on the homogeneous anionic SAMs are mainly responsible for high surface density of PGG-GDH and this might bring higher detection sensitivity in the glucose sensing.…”
Section: Resultssupporting
confidence: 65%
“…Based on self-assembled monolayer (SAM) method, a protein layer can be fabricated by binding proteins to a substrate either covalently (chemical coupling) or non-covalently (physical absorption) [9-12], but the covalent method is superior due to its good reproducibility and homogeneity in layer formation [13,14]. In addition, it has been demonstrated that the substrate surface can be chemically modified easily and efficiently to tailor a specific protein layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, covalent immobilization achieves probe directionality, reduces background noise, and develops a stable biomolecule layer. 3,4 Indeed, this strategy has been employed for the vast majority of commercial products because of its versatility, durability, and good functionality. 5,6 Covalent linking of probes on optical disks requires functionalization of the surface since polycarbonate (PC), the main component of disks, lacks appropriated reactive chemical groups.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electrostatic immobilization of DNA probes on positively charged surfaces, e.g., amino-silanized glass or charged-nylon membranes, is a common strategy to attach them in a random manner. However, covalent immobilization achieves probe directionality, reduces background noise, and develops a stable biomolecule layer. , Indeed, this strategy has been employed for the vast majority of commercial products because of its versatility, durability, and good functionality. , …”
Section: Introductionmentioning
confidence: 99%